MENNESKELIG HANDLING: Illusionen som dramatisk grundvilkår - Hastrup, Kirsten (Tidsskriftet Antropologi, 2000)
Taking the point of departure in the world of Shakespeare and his players, it is argued that illusion has nothing to do with deception or delusion. Rather it is seen as a suspense of form, a waiting for the fulfilment of the plot. This view is extended to the social world in general, where an illusion of wholeness and plot is also a precondition for action: without a sense of context, no one can act adequately. Players of Shakespeare are double agents, in that they have to act as both actor and character; again, it is argued that human agency is always a kind of double agency, requiring an awareness of both one’s own practical skills and the entire social drama in which one participates. In short, both on and off stage, acting in character means abiding to an over-all illusion about a whole that is but suspended form.